PENGARUH REKRUTMEN, SELEKSI KARYAWAN DAN PENEMPATAN KARYAWAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. BATAM TV, PROVINSI KEPULAUAN RIAU - Sumardin (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2022)
This research was conducted at Batam TV Company, Riau Islands Province. The number of respondents used in this study were 38 respondents. The research tools used in collecting data were 38 respondents. The data analysis tool used is SPSS 17.00. In testing the hypothesis whether the Recruitment variable has an effect on Employee Work Productivity, because t count (7.781) > t table (1.688), Ho is rejected and H1 is accepted, meaning; Significant regression coefficient or Employee Recruitment variable has an effect on Work Productivity. In testing the hypothesis whether the employee selection variable has an effect on employee productivity, then because t count (10,788) > t table (1,688), Ho is rejected and H1 is accepted, meaning; The regression coefficient is significant or the Employee Selection variable has an effect on the Work Productivity variable. In testing the hypothesis whether the Employee Placement variable has an effect on Employee Work Productivity, then because t count (6.092) > t table (1.688), Ho is rejected and H1 is accepted, meaning; The significant regression coefficient or the Employee Placement variable has an effect on the Employee Productivity variable. In testing the hypothesis whether the variables of Employee Recruitment, Employee Selection and Employee Placement simultaneously affect Employee Work Productivity. The ANOVA test resulted in a calculated F number of 43.986 > F table 2.88 with a significance level (probability number) of 0.05. F count > F table then Ho is rejected and H1 is accepted. Then the regression coefficients of Employee Recruitment, Employee Selection and Employee Placement together have a significant effect on the Work Productivity variable.